A Case of Secondary Hemophagocytic Lymphohistiocytosis Presenting with Severe Dyserythropoeisis in a Patient with Autoimmune Hemolysis - Kai J. Rogers; Sharathkumar Bhagavathi (Case Reports in Hematology)
The diagnosis of hemophagocytic lymphohistiocytosis (HLH) requires that several clinical criteria are met, and often relies on the identification of rare hemophagocytic cells in the bone marrow. Given the challenge in making the diagnosis, additional signs of immune dysregulation in the bone marrow would have practical clinical use in cases where overt hemophagocytosis is not seen. We present here a case of secondary HLH in a patient with autoimmune hemolysis ultimately diagnosed as Evans syndrome that initially presented with profound dyserythropoeisis in both the peripheral blood and bone marrow. We also explore an association between dyserythropoeisis and HLH in a series of cases previously seen at our institution.